2014
DOI: 10.1039/c4ta01319k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical supercapacitor with polymeric active electrolyte

Abstract: An electrochemical supercapacitor with a polymeric active electrolyte was designed and fabricated in this work. A water-soluble conducting polymer, sulfonated polyaniline (SPAni), was used in the supercapacitor as the active electrolyte and a semipermeable membrane was employed as the separator of the device. It was found that SPAni in the electrolyte can provide pseudocapacitance via its reversible electrochemical redox reaction. Owing to the good stability of SPAni, the supercapacitor has a long cycling life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 32 publications
0
82
0
Order By: Relevance
“…Apart from the preparation of 3D graphene through chemical reduction method with the aid of reducing agent, electrochemical reduction of GO in aqueous solution is thought to be a green and effective route to prepare 3D graphene. For example, Chen et al [ 77 ] fabricated 3D porous graphene‐based composite materials through a facile and universal template‐free approach composed of two consecutive electrochemical steps ( Figure 17 a). Highly porous and conductive 3D graphene was directly deposited onto the copper foil surface followed by the successive electrochemical deposition of the targeted filler material, giving rise to a 3D graphene‐based composite architecture.…”
Section: Synthesis Methods Of 3d Graphenementioning
confidence: 99%
“…Apart from the preparation of 3D graphene through chemical reduction method with the aid of reducing agent, electrochemical reduction of GO in aqueous solution is thought to be a green and effective route to prepare 3D graphene. For example, Chen et al [ 77 ] fabricated 3D porous graphene‐based composite materials through a facile and universal template‐free approach composed of two consecutive electrochemical steps ( Figure 17 a). Highly porous and conductive 3D graphene was directly deposited onto the copper foil surface followed by the successive electrochemical deposition of the targeted filler material, giving rise to a 3D graphene‐based composite architecture.…”
Section: Synthesis Methods Of 3d Graphenementioning
confidence: 99%
“…As generally realized, the choice of separator materials depends on the type of electrode, working temperature and ES cell voltage. 430,436 Recently, some new separator materials, such as GO films 492 and eggshell membranes, 493 have been explored for ESs. Bittner et al 476 found that the trace amount of water in the organic electrolyte (TEABF 4 /ACN) could play a role in accelerating the ageing process of EDLCs when a cellulose separator was used.…”
Section: Separatorsmentioning
confidence: 99%
“…As for the failure prediction for PP‐rich blends, it may be attributed to the asymmetric viscoelasticity between PP and HDPE. In the work of Chen and Wu, the highly asymmetric in their viscoelasticity of the Poly(trimethylene terephthalate)/poly(butylenes succinate) (PTT/PBS) blends affects the description of Palierne's emulsion model. At the same temperature PP has higher elasticity and viscosity than HDPE.…”
Section: Resultsmentioning
confidence: 99%